2021
DOI: 10.3892/mmr.2021.11990
|View full text |Cite
|
Sign up to set email alerts
|

Updates in neonatal coronavirus disease 2019: What can we learn from detailed case reports? (Review)

Abstract: Although the COVID-19 epidemic has lasted for months, it has not yet been successfully controlled, and little is known about neonatal COVID-19. Therefore, literature search was conducted for references in PubMed, Science Direct, ProQuest, Web of Science and China National Knowledge Infrastructure for detailed case reports on neonatal COVID-19 published as of July 15, 2020, to facilitate the clinical treatment, epidemic prevention and control of neonatal COVID-19. Forty nonoverlapping case reports focusing main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“… 23 At present, the effect of caesarean section on the vertical transmission of COVID-19 is not clear. 24 Cases of coinfection with SARS-CoV-2 in newborns born to mothers perinatally infected with SARS-CoV-2 are rare. 25 However, because mothers who have been infected with SARS-CoV-2 at the time of delivery are still infectious, newborns are still at risk of contracting the virus from their mothers.…”
Section: Epidemiological Characteristics Of Covid-19 In Childrenmentioning
confidence: 99%
“… 23 At present, the effect of caesarean section on the vertical transmission of COVID-19 is not clear. 24 Cases of coinfection with SARS-CoV-2 in newborns born to mothers perinatally infected with SARS-CoV-2 are rare. 25 However, because mothers who have been infected with SARS-CoV-2 at the time of delivery are still infectious, newborns are still at risk of contracting the virus from their mothers.…”
Section: Epidemiological Characteristics Of Covid-19 In Childrenmentioning
confidence: 99%
“…Those with severe complications were a preterm newborn child and a 2-month-old infant (15). A recent review of the literature reported 40 new-borns with no persistent abnormalities (21). Whittaker et al showed that children <1 year-old on admission were 27.5% of the total number of children hospitalized for pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…An adequate follow-up of at least 2 weeks was recommended in most instances so that the clinician can define the outcome (15). Short-and long-term outcomes are still unclear in newborns (21). The long-term effect of COVID-19 infection on lung parenchyma and pulmonary function remains unknown in the pediatric age group (23).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, vertical transmission of SARS-CoV-2 from maternal blood to the fetus could occur [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. Finally, the child could be infected by the mother after birth, during delivery or through breastmilk [ 89 , 90 , 91 ].…”
Section: Factors Supporting the Immunization Of Pregnant Women Against Covid-19mentioning
confidence: 99%
“…The transmission of SARS-CoV-2 during delivery or through breast milk can also be considered very rare [ 89 ]. Ascending infection has never been demonstrated, and vaginal delivery is not more common than caesarean section among children with suspected SARS-CoV-2 infection [ 69 ].…”
Section: Factors Supporting the Immunization Of Pregnant Women Against Covid-19mentioning
confidence: 99%